USED OR WORN HYDROTECHNICS OF IN SH OOTS SECURITY AND RELIABILITY TA ’ MINLA SH - O'. O'. Rajabov (Scientific Impulse, 2023)
In this article, increasing the safety and reliability of modern hydrotechnical facilities of the Republic of Uzbekistan. It is assumed that as a result of many years of use of hydraulic structures, their physical and spiritual wear and tear and their technical capabilities and reliability are decreasing.